2007
DOI: 10.2460/javma.230.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oxacillin- and multidrug-resistant staphylococci in clinical samples from dogs: 1,772 samples (2001–2005)

Abstract: Veterinarians should be aware of the potential for empiric drug treatment failures in instances where Staphylococcus spp infections are common (eg, pyoderma). Judicious use of bacterial culture and susceptibility testing is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
3
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 31 publications
6
116
3
5
Order By: Relevance
“…Como o aumento da prevalência de MRSP em cães com pioderma superficial é um acontecimento relativamente recente (Jones et al 2007, Loeffler et al 2007, Lucia et al 2011, torna-se importante a avaliação local e periódica dos perfis de suscetibilidade. Como já mencionado, as cefalosporinas são os antimicrobianos de primeira escolha e utilizados com maior frequência no tratamento dessa dermatopatia, entretanto, frente a infecções cutâneas por MRSP, as cefalosporinas deixam de constituir opções terapêuticas, o que restringe a seleção dos fármacos.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Como o aumento da prevalência de MRSP em cães com pioderma superficial é um acontecimento relativamente recente (Jones et al 2007, Loeffler et al 2007, Lucia et al 2011, torna-se importante a avaliação local e periódica dos perfis de suscetibilidade. Como já mencionado, as cefalosporinas são os antimicrobianos de primeira escolha e utilizados com maior frequência no tratamento dessa dermatopatia, entretanto, frente a infecções cutâneas por MRSP, as cefalosporinas deixam de constituir opções terapêuticas, o que restringe a seleção dos fármacos.…”
Section: Resultsunclassified
“…Dentre os multirresistentes, em 24 verificou--se resistência a três classes de antimicrobianos, em 11 a quatro classes e um isolado frente a cinco classes (Quadro 1). Embora a multirresistência tenha íntima associação com estafilococos resistentes à meticilina em humanos e animais, esse padrão pode ocorrer na ausência de resistência à oxacilina (Jones et al 2007), fato observado neste estudo, no qual cinco dos 36 isolados multirresistentes, também foram resistentes à oxacilina. Onuma et al (2011) relataram expressiva elevação na prevalência de multirresistência entre S. pseudintermedius isolados de cães com pioderma no Japão, entre 1999 e 2009.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…In antimicrobial susceptibility interpretation, the fact that methicillin resistance is mediated by mecA gene, that confers resistance to all β-lactam antibiotics, should be taken into account, regardless of the in vitro results (Jones et al, 2007). The same applies to macrolides because of their cross-resistance (Ganiere et al, 2005).…”
Section: Methicillin-resistant S Pseudinter-medius (Mrsp)mentioning
confidence: 99%
“…For example, in the Netherlands, there was an increase from 0.9% in 2004 to 7% in data published in 2016. [5][6][7][8][9][10][11][12][13] Vanessa Schmidt concluded that MDR strains were common in the population studied. It is increasingly important to obtain bacterial cultures before treatment.…”
mentioning
confidence: 96%